Does Co-worker Presenteeism Increase Innovative Behavior? Evidence From IT Professionals Under the 996 Work Regime in China - Yang, Tianan; Liu, Ran; Deng, Jianwei (Frontiers in Psychology, 2021)
Drawing on the event system and regulatory focus theory, this study constructed an impact mechanism model to investigate the relationship between the event strength of co-worker presenteeism and innovative behavior among IT professionals under the 996 work regime. In addition to test the direct effect, we examined the indirect effect of promotion focus and the moderating effect of event time in this relationship. Data were collected through an online survey administered to 374 IT professionals in China. The results showed a positive relationship between the criticality of co-worker presenteeism events and innovative behavior. An indirect effect of promotion focus was also found in this relationship. The timing of co-worker presenteeism events moderated the relationship between the criticality of co-worker presenteeism events and promotion focus. Specifically, the effect was more significant when co-worker presenteeism events occurred during project delays.